Unintentional Injury, Psychological Distress and Depressive Symptoms: Is There an Association for Rural Australians?. Issue 1 (2nd August 2012) - Fragar, Lyn; Inder, Kerry J.; Kelly, Brian J.; Coleman, Clare; Perkins, David; Lewin, Terry J.
Abstract Purpose: To investigate the association between unintentional injury and mental health in Australian rural communities. Methods: Using cross‐sectional baseline data for a longitudinal study from randomly selected adults in nonmetropolitan Australia, we fitted logistic regression models for the outcomes of domestic or public setting injury and injury in high‐risk settings, using prior depression and demographic factors. OR and 99% CI were reported and also calculated for current mental health including psychological distress, depressive symptoms and risky alcohol consumption, comparing those injured with those not. Findings: Of 2, 639 participants who completed the injury component, 364 (13.8%) reported injury requiring treatment from a doctor or a hospitalization in the previous 12 months. Of those requiring treatment or hospitalization, 147 (40.4%) reported being injured in a domestic or public setting and 207 (56.9%) in a high‐risk setting. The most common types and mechanisms of injury were sprains and strains, and falls, trips and slips, respectively. Preinjury depression was independently associated with unintentional injury in a domestic or public setting. Being injured in this setting was associated with double the odds of experiencing current depressive symptoms. The likelihood of a high‐risk setting injury was significantly associated with male gender. High‐risk setting injury was associated with current psychological distress and higher levels of alcohol usage. Conclusions: This study supports the hypothesis that pre‐existing depression is associated with unintentional injury in a rural sample and indicates the important role of prior depression in management of injury, given the high rate of injury in rural communities. Mechanisms by which prior depression increases likelihood of unintentional injury will be further investigated using longitudinal data.